GE_GERICHTE C/19647/2011 vom 27. April 2012 - GE Cour de justice (2012)
; DÉPENS ; CALCUL | Principes de calcul de l'indemnité due à titre de dépens. | LP.82. CPC.95. CPC.96. LaCC.16. LaCC.18. RTFMC.84. RTFMC.85. RTFMC.89. RTFMC.88